Pengaruh independensi, kompetensi, moral reasoning dan skeptisisme profesional auditor pemerintah terhadap kualitas audit laporan keuangan pemerintah daerah (studi empiris pada BPK RI perwakilan provinsi Riau) - Eveline Roirianti Naibaho; Hardi '; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research to know the partial effect of independence, competence, moral reasoning and professional skepticism of government auditor to audit quality of local government financial statement. The technique used to collect the data in this research is using questionnaire which was sent directly to the BPK RI Representative of Riau Province. The total of respondents used in this research is 43 respondents (81.13%). The method of data analysis used is the multiple linear regression using SPSS (Statistical Product and Service Solutions) Version 17. The result of this research indicate that partially, independence, competence, and moral reasoning of government auditor have influence to audit quality of local government financial statement, while professional skepticism of government auditor does not have influence to audit quality of local government financial statement. The determination coefficient of this research is 77.6%. The four variables have influenced to the dependent variable at the same time as much as 77.6%, while 22.4% has influenced by another variable that is not explained in this research.Keywords : Audit Quality, Independence, Competence, Moral Reasoning, and Professional Skepticism.